Determination of the Changes in Airborne Ba and Mn Concentrations in Düzce City Center in the Last 40 Years with the Help of Cedrus atlantica Annual Rings - USLU, Sümeyya; YİĞİT, Nurcan (Kastamonu University, 2023)
Heavy metals are pollutants that pose a great threat to humans, other living things, and the ecosystem. All barium (Ba) compounds, one of the most dangerous and harmful heavy metals, are poisonous. Manganese (Mn) is a harmful heavy metal that can cause hallucinations, fatigue, insomnia, weakness, forgetfulness, nerve damage, Parkinson's, and lung embolism. Therefore, observing the changes in Ba and Mn concentrations in the air is essential. This study aimed to determine the change of Ba and Mn heavy metals in the Cedrus atlantica tree based on direction, period, and organ. As a result, the annual rings of Cedrus atlantica show that the transfer of both heavy metals into the wood of Cedrus atlantica was limited. Therefore, the species is a suitable biomonitor that can be used to monitor the changes in Ba and Mn concentrations in the air. In addition, the study results revealed that the concentrations of both elements in the outer barks are quite high, and Ba pollution is primarily caused by traffic.
Keywords: Atlas cedar; Annual ring; Biomonitor; Barium; Manganese; Plant Physiology; Bitki Fizyolojisi; 13. Climate action; 15. Life on land